2006
DOI: 10.1002/hbm.20265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the spatial relationship of event‐related potential and functional MRI sources in the primary visual cortex

Abstract: The integration of electroencephalogram (EEG) recordings and functional magnetic resonance imaging (fMRI) can provide considerable insight into brain functionality. However, the direct relationship between neural and hemodynamic activity is still poorly understood. Of particular interest is the spatial correspondence between event-related potential (ERP) and fMRI sources. In the current study we localized sources generated by a checkerboard stimulus presented to eight subjects using both EEG and fMRI. The loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 53 publications
4
19
0
Order By: Relevance
“…S5) indicate that, at the level of the false discovery rate threshold used, there were no brain regions in which the P100 amplitude was informative about the HRF amplitude. This is in accordance with our previous work, where the absolute values of activity dependence were low and not significantly different to zero , see also (Whittingstall et al, 2007). This null result highlights the need for a more detailed investigation of the EEG signal space to identify features which carry information about the haemodynamic response.…”
Section: Discussionsupporting
confidence: 94%
“…S5) indicate that, at the level of the false discovery rate threshold used, there were no brain regions in which the P100 amplitude was informative about the HRF amplitude. This is in accordance with our previous work, where the absolute values of activity dependence were low and not significantly different to zero , see also (Whittingstall et al, 2007). This null result highlights the need for a more detailed investigation of the EEG signal space to identify features which carry information about the haemodynamic response.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, fMRI activation maps show that in response to brief light stimuli, most of the activated voxels are located in the primary visual cortex (Figure 1). This is in agreement with a similar study where it was reported that the early VEP component is localized closer to the V1 BOLD response than the later VEP component (Whittingstall et al, 2007(Whittingstall et al, , 2008. On the other hand, other studies have shown that different evoked potential deflections correlate best with the BOLD response, for example, P3a is related to BOLD signal changes in the right fusiform and left superior temporal gyrus for a facial emotion recognition task (Johnston et al, 2005); N170 for face and house visual stimuli have been found to correlate well with hemodynamic responses in various brain areas in the temporaloccipital lobes (Iidaka et al, 2006); and N400 and BOLD signals were linked in the superior temporal gyrus for a semantic priming task (Matsumoto et al, 2005).…”
Section: Link Between Blood Oxygenation Level-dependent Signal and VIsupporting
confidence: 94%
“…Indeed, visual information coming from the right visual hemifield is conveyed to the left occipital visual areas (and vice-versa for the left visual hemifield) via both ipsilateral and contralateral pathways. Such predominant contralateral activity in response to peripherally presented pictures was already found with fMRI [46], magnetoencephalography [47] or visual evoked potentials [48] but never at such eccentric locations. The lateralization of the early visual activity could also be related to a more extended and direct innervation of secondary and more lateral areas by the magnocellular pathway, as suggested by a few studies in animals ( [49] in monkeys; [50] in cats).…”
Section: Effects Of Eccentricity On Early Visual Erpsmentioning
confidence: 52%